THE USE OF DIETHANOLAMINE AS A CO2 ABSORBENT IN WAS TAKE THE DETERMINATION CORAL REEF AGE IN BARRANG LOMPO ISLAND SPERMONDE ISLANDS THROUGH MEASUREMENTS OF 14C ACTIVITY BY LIQUID SCINTILLATION COUNTING (LSC) METHOD - Jumiati Bunga Matande; Muhammad Zakir; Alfian Noor (Marina Chimica Acta, 2017)
Research on the use of diethanolamine (DEA) as a CO2 absorbent in was take the determination coral reef age in Barrang Lompo Island, Spermonde Islands through measurements of 14C activity by liquid scintillation Counting method (LSC) was carried our. Coral reef sample of the island Barrang Lompo at coordinates 5 ° 06 '49 " LS 119 ° 25' 20" BT with a dept of 3-4 meters from the sea surface. Coral reefs (coral reef) is an ecosystem that live on the water in the form of limestone formations (CaCO3). Sample preparation is done physically and chemically. Chemical preparation of coral reef sample was using 30% H2O2 continued with HClO4 mixture and H2O2 30% and the last with a solution of HCl to produce a clean sample with a weight reduction of 16.318%. Carbonate samples separated as CO2 by reaction with 10% HCl and absorbtion by diethanolamine  to produce carbamate compounds with 62.236% efficiency. Total carbon in the sample solution is obtained through a 1,709 gram reduction methods before and after absorption. Radiocarbon dating method is based on measuring the specific activity of the samples obtained from the results of the count Liquid Scintillation Counting (LSC) Hidex 300 SL, which is 7.938192 dpm/gC. The specific activity of the age of the coral reefs are estimated 5425.452 year